Rancang Bangun Aplikasi Posyandu Berbasis Web untuk Meningkatkan Kinerja Kader Studi Kasus : Posyandu Gagak - Destria Aldesyar; Budi Jejen Zaenal Abidin; Angge Firizkiansah (Universitas Sains Indonesia Publishing, 2026)
The rapid development of information technology has encouraged various public service sectors, including healthcare services, to utilize information systems in improving service quality. Posyandu Gagak still performs data recording manually using handwritten records, causing difficulties in data management, reporting, and monitoring the development of pregnant women, infants, and toddlers. This study aims to design and develop a web-based Posyandu application to improve cadre performance in managing Posyandu activities. The system was developed using a web-based information system approach with features including login, management of pregnant women data, infant and toddler data, health examinations, activity schedules, and reporting. The implementation of the system is expected to improve efficiency, accuracy, and effectiveness in Posyandu data processing and reporting activities. Based on system testing using the Black Box Testing method, all system features functioned properly according to user requirements.